AMBRA1-Mediated Mitophagy Counteracts Oxidative Stress and Apoptosis Induced by Neurotoxicity in Human Neuroblastoma SH-SY5Y Cells - Di Rita, Anthea; D’Acunzo, Pasquale; Simula, Luca; Campello, Silvia; Strappazzon, Flavie; Cecconi, Francesco (Frontiers in Cellular Neuroscience, 2018)
Therapeutic strategies are needed to protect dopaminergic neurons in Parkinson’s disease (PD) patients. Oxidative stress caused by dopamine may play an important role in PD pathogenesis. Selective autophagy of mitochondria (mitophagy), mainly regulated by PINK1 and PARKIN, plays an important role in the maintenance of cell homeostasis. Mutations in those genes cause accumulation of damaged mitochondria, leading to nigral degeneration and early-onset PD. AMBRA1ActA is a fusion protein specifically expressed at the mitochondria, and whose expression has been shown to induce a powerful mitophagy in mammalian cells. Most importantly, the pro-autophagy factor AMBRA1 is sufficient to restore mitophagy in fibroblasts of PD patients carrying PINK1 and PARKIN mutations. In this study, we investigated the potential neuroprotective effect of AMBRA1-induced mitophagy against 6-hydroxydopamine (6-OHDA)- and rotenone-induced cell death in human neuroblastoma SH-SY5Y cells. We demonstrated that AMBRA1ActA overexpression was sufficient to induce mitochondrial clearance in SH-SY5Y cells. We found that apoptosis induced by 6-OHDA and rotenone was reversed by AMBRA1-induced mitophagy. Finally, transfection of SH-SY5Y cells with a vector encoding AMBRA1ActA significantly reduced 6-OHDA and rotenone-induced generation of reactive oxygen species (ROS). Altogether, our results indicate that AMBRA1ActA is able to induce mitophagy in SH-SY5Y cells in order to suppress oxidative stress and apoptosis induced by both 6-OHDA and rotenone. These results strongly suggest that AMBRA1 may have promising neuroprotective properties with an important role in limiting ROS-induced dopaminergic cell death, and the utmost potential to prevent PD or other neurodegenerative diseases associated with mitochondrial oxidative stress.